TT¯-deformations, AdS/CFT and correlation functions - Giribet, Gaston (The journal of high energy physics, 2018)
A bstract A solvable irrelevant deformation of AdS 3 /CFT 2 correspondence leading to a theory with Hagedorn spectrum at high energy has been recently proposed. It consists of a single trace deformation of the boundary theory, which is inspired by the recent work on solvable T T ¯ deformations of two-dimensional CFTs. Thought of as a worldsheet σ -model, the interpretation of the deformed theory from the bulk viewpoint is that of string theory on a background that interpolates between AdS 3 in the IR and a linear dilaton vacuum of little string theory in the UV. The insertion of the operator that realizes the deformation in the correlation functions produces a logarithmic divergence, leading to the renormalization of the primary operators, which thus acquire an anomalous dimension. We compute this anomalous dimension explicitly, and this provides us with a direct way of determining the spectrum of the theory. We discuss this and other features of the correlation functions in presence of the deformation.